MANAGERIAL TEAM: MODERN TECHNOLOGIES OF TEAM BUILDING - В. І. Борщ; Д. В. Бевзюк (Ринкова економіка: сучасна теорія і практика управління, 2018)
The article considers modern methods of forming a management team. The main goal of this process is its effectiveness support. The problem of the formation and effective work of the management team at the enterprise is viewed. Modern methods of forming a management team are considered. Among such methods we can notice, such as goal-oriented (based on goals), interpersonal, role-oriented and problem-oriented. The stages of team development process are considered. The consistency of the stages of the management team formation is determined by the group’s subculture.